The Computerized Problem-Oriented Medical Record at Karolinska Hospital — Format and Function, Users’ Acceptance and Patient Attitude to Questionnaire — - Mellner, Ch.; Selander, H.; Wolodarski, J. (Methods of Information in Medicine, 1976)
In the last five years computerized medical records have come into routine use at some departments of the Karolinska Hospital. These records were to a large extent based on the problem-oriented approach.This paper describes the format and function of this record, reports the acceptability thereof to the users compared to the traditional source-oriented medical record, and discusses patient attitudes to the questionnaire method for medical history-taking.
Keywords: Computerized Problem-oriented Medical Record; History Taking; Questionnaire